2015
DOI: 10.1364/ol.40.003739
|View full text |Cite
|
Sign up to set email alerts
|

Laguerre–Gauss beams versus Bessel beams showdown: peer comparison

Abstract: We present for the first time a comparison under similar circumstances between Laguerre-Gauss beams (LGBs) and Bessel beams (BB), and show that the former can be a better option for many applications in which BBs are currently used. By solving the Laguerre-Gauss differential equation in the asymptotic limit of a large radial index, we find the parameters to perform a peer comparison, showing that LGBs can propagate quasi-nondiffracting beams within the same region of space where the corresponding BBs do. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…It has also been shown that optical information protocols may benefit from the radial degree of freedom [6 8]. The role played by the radial features of a light field within the classical picture has also been explored, for instance regarding its diffraction properties [9], but mainly in the context of the creation of pure LG modes. Contactless optical manipulation is another classical optics application example, where the super position of LG modes including at least one high order radial mode is used to create rotating beams [10,11] or so called bottle beams [12].…”
mentioning
confidence: 99%
“…It has also been shown that optical information protocols may benefit from the radial degree of freedom [6 8]. The role played by the radial features of a light field within the classical picture has also been explored, for instance regarding its diffraction properties [9], but mainly in the context of the creation of pure LG modes. Contactless optical manipulation is another classical optics application example, where the super position of LG modes including at least one high order radial mode is used to create rotating beams [10,11] or so called bottle beams [12].…”
mentioning
confidence: 99%
“…6. We also observe the behavior on Bessel beams with the same transverse section and spa- tial frequency for comparison, as in the work done by Mendoza-Hernández et al [42]. Figure 6(a) shows the LGB in the first row and Bessel beam (BB) in the second row, partially blocked.…”
Section: Experimental Generation Of Incoming and Outgoing Wavesmentioning
confidence: 54%
“…6 (a). In comparison, the BG modes show resilience thanks to the multiple concentric rings [58]. LG 0 1 2…”
Section: Resultsmentioning
confidence: 99%